INVESTIGATING STUDENTS' ONLINE CRITICAL READING SKILL: A STUDY IN AN EFL CONTEXT - Kurniati, Nur Utami Sari'at (STKIP Persada Khatulistiwa Sintang, 2024)
The digital lifestyle requires students to read any online discourse more critically. The paper presents the result of a study in which 42 EFL learners are asked to demonstrate their critical reading skills through answers to the questionnaire and test. Both instruments are adapted from Cottrell's (2011). The participants are intermediate EFL learners in Indonesia. They are 19-20 years of age, male and female. All of them enroll the Discourse Analysis course. The result reveals that most of them have a positive attitude and give a positive response to some key questions under the critical thinking skills. They show the ability to identify unfair techniques used in a text and are good at reading between and beyond the lines. They do further research when they are hesitant about something they read and know how to evaluate source material. With some refinements and piloting, future research might be done on other language skills.